Teacher Coaching: Increasing Deaf Students' Active Engagement Through Flexible Instructional Arrangements. (30th September 2021) - Catalano, Jennifer; Weirick, Whitney; Hasko, Janna; Antia, Shirin
Abstract: The study examined the effects of a coaching intervention on teachers' ability to implement academically responsive instruction through flexible instructional arrangements in self-contained classrooms for students who are deaf and hard of hearing, as well as the impact of instructional arrangements on students' academic engagement. Using a changing criterion design replicated across teachers, three-teacher participants with diverse backgrounds received differentiated coaching to implement flexible instructional arrangements. Results showed that coaching had an impact on all three teachers' implementation of flexible instructional arrangements. Concomitantly, students increased their active engagement and decreased passive engagement when they spent less time in whole class and more time in small group and child-managed arrangements. Teachers maintained the use of flexible instructional arrangements and students continued to be more actively engaged than pre-intervention. Limitations and implications for practice and research are discussed.